Envy in mission-oriented organizations - Francesca Barigozzi; Ester Manna (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
According to the labor donation theory, workers adhering to their firms' mission are willing to donate a portion of their paid labor. In this paper, we study how workers' fairness concerns limit the firm's ability to extract labor donation from its employees. We find that, in sectors where the firm's mission is important, optimal contracts are such that high-ability employees perceive their wage as less fair than low-ability employees and they must be rewarded with an "envy rent". The opposite is true in sectors where the firm's mission does not play a relevant role. We empirically test the predictions of the model using the German Socio-Economic Panel finding support for our theoretical results.
Keywords: D03; D82; M54; 330; Mission-oriented organizations; envy; labor donations; screening